Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1063/1.1483301
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of periodic arrays of cylinders for viscoelastic flows

Abstract: In this paper we numerically investigate the motion of viscoelastic liquids passing through two-dimensional periodic arrays of cylindrical particles using the finite element method. The viscoelastic liquid is modeled by the Chilcott–Rallison version of the finitely extensible, nonlinear elastic (FENE) dumbbell model. The permeability and the viscoelastic stress distribution are studied as functions of the dimensionless relaxation time De and the dimensionless wave number kD, where k=2π/λ is the wave number, λ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
2
17
0
6
Order By: Relevance
“…These trends also match very well with recent observations by Talwar et al [19] who studied the flow of polymer solutions through periodic arrays of cylinders as well as others [17,19,24,26,27,46,[61][62][63]. They reported a dimensionless drag in terms of the product of the friction factor and the Reynolds number fRe.…”
Section: Pressure Dropsupporting
confidence: 91%
“…These trends also match very well with recent observations by Talwar et al [19] who studied the flow of polymer solutions through periodic arrays of cylinders as well as others [17,19,24,26,27,46,[61][62][63]. They reported a dimensionless drag in terms of the product of the friction factor and the Reynolds number fRe.…”
Section: Pressure Dropsupporting
confidence: 91%
“…Numerical simulations have also proved to be a valid tool to investigate viscoelastic flows in porous media, uncovering the details of the fluid deformation and stresses. Alcocer and Singh [24] studied the viscoelastic flow through an array of cylinders using the finite element method and a FENE (finitely extensible nonlinear elastic) model for the stresses. These authors have shown the influence of the cylinder distribution and Deborah number on the permeability of the medium.…”
Section: Non-newtonian Flow In Porous Mediamentioning
confidence: 99%
“…However the validity of this macroscopic approach remains largely limited to Newtonian flows. In theoretically understanding viscoelastic creeping flows in porous media, much of the progress has been made computationally [15][16][17][18][19][20][21]. Early simulations of two-dimensional (2D) viscoelastic flow past a bi-periodic square [15,16] or rectangular [17] array of cylinders observed a slightly reduced pressure drop at low Weissenberg numbers compared to that of a Newtonian fluid of matched viscosity, as seen experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Alcocer et al [19,20] investigated 2D flow of the FENE-CR model past a biperiodic array of cylinders, with a particular focus on the dependence of the effective permeability on the cell aspect ratio, for a fixed area fraction of cylinders. They demonstrated a non-monotonic dependence of permeability on aspect ratio.…”
Section: Introductionmentioning
confidence: 99%